IMPLEMENTASI RESTORATIVE JUSTICE TERHADAP KEKERASAN SEKSUAL SECARA VERBAL (STUDI KASUS DI TROWULAN MOJOKERTO) - Dewi, Dwi Ratna Cinthya; Ilmiya, Suci Syamrotul; Listi, Lathifa Adi (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2022)
The crime of immorality began when a young man in Jambuwok Village, Trowulan District, committed acts that were considered to violate the norms of social good faith. A young man (AS) often peeked and stole his underwear and disturbed nearby citizens. These events were resolved in a restorative juctice manner by peaceful means. This type of research is field research (field reserch) with data search for the application of restorative justice in cases of verbal sexual violence. This study is the result of a study of an empirical juridical approach that aims to study and analyze the function of law in society that is manifested in the legal behavior of society. The case approach aims to study between legal theory and practice in the implementation of positive law regarding restorative juctice in cases of sexual harassment. All parties involved in the matter. The process of resolving immoral crimes committed in Trowulan is mediated by the village head, in accordance with the concept of restorative justice, namely through deliberations with all parties to maintain a sense of justice. It ended peacefully without hurting anyone.